Advancements of 2D Materials-Based Membranes - Zakarya Othman (11778968) (2021)
Our environment desperately needs creative solutions to limit the effect of industrialization’s fast rise and, consequently, to remediate vast amounts of harmful by-products and toxic exhausts. Day by day, nanomaterials are becoming a more viable and eco-friendly option for efficient environmental remediation. Due to their large surface area, high reactivity, enhanced redox, and photocatalytic properties, a variety of nanomaterials are identified as ideal adsorbents, catalytic and antibacterial agents, as well as functional membranes. Among the emerging nanomaterials, 2D nanomaterials have attracted increasing attention recently following the discovery of graphene, which quickly placed among the most promising materials due to its distinctive structures and novel properties. Moreover, the discovery of graphene has paved the way for the synthesis of various 2D materials. Around 20 different types of 2D nanomaterials have been reported to date, including graphene, MXenes, graphitic carbon nitride (g-C3N4), black phosphorus (BP), metal phosphorus trichalcogenides, hexagonal boron nitride (h-BN), transition metal dichalcogenides (TMDs), and 2D polymers. As a result of the quantum confinement effects, and the dependence on material’s composition, atomic arrangement, and layer thickness, these 2D nanomaterials display an array of exceptional electronic, optical, physical, and chemical properties that are quite unique. Therefore, by developing advanced, functional 2D nanomaterial-based membranes, we may achieve a new level of efficiency, selectivity, sensitivity, and mechanical stability, all of which are critical for environmental remediation applications. Other Information Published in: Membranes License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/membranes12010052